2020
DOI: 10.2478/ats-2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and economics of integrated weed management in okra (Abelmoschus esculentus (L.) Moench)

Abstract: Weed management is one of the most important and expensive steps in okra production. Field experiments were therefore conducted in the early and late wet seasons of 2015 to evaluate the effectiveness and profitability of weed management using hoe weeding, herbicides or their combination in okra production. Propaben or butachlor at 2.0 kg a.i. (active ingredient) ha–1 followed by (fb) supplementary hoe weeding (shw) at 6 weeks after sowing (WAS) significantly (P < 0.05) reduced weed density and biomass with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In our study, different types of mulches showed a significant effect on weed suppression compared with the control. This reaffirms the ability of mulches, regardless of the material used, to exert a physical effect on weed suppression and weed seed germination [37]. It is important to note that both GEO and HAZ mulches showed greater efficacy in soil moisture retention.…”
Section: Weeds Soil Moisture and Temperature And Leaf Temperaturesupporting
confidence: 63%
“…In our study, different types of mulches showed a significant effect on weed suppression compared with the control. This reaffirms the ability of mulches, regardless of the material used, to exert a physical effect on weed suppression and weed seed germination [37]. It is important to note that both GEO and HAZ mulches showed greater efficacy in soil moisture retention.…”
Section: Weeds Soil Moisture and Temperature And Leaf Temperaturesupporting
confidence: 63%